Multimedia resources adoption and use among distance learning students at University of Ibadan study centre (2020)
Purpose: This study examined the adoption and use of multimedia resources by distance learning students at University of Ibadan study centre. Design/Methodology/Approach: Descriptive survey research design was adopted for this study. Four objectives were formulated to guide the study. Simple random sampling technique was used to sample 10% of the total population which gave a 532 sample size. The structured questionnaire was the main instrument used for data collection. A total of 532 copies of questionnaire were administered to the students at the faculty of education, 490 copies were duly completed and returned with a response rate of 92.1%. The data collected were analyzed using SPSS with frequency counts and percentages. Findings: The findings revealed that majority of the respondents affirmed that multimedia resources such computers, the internet services, mobile/cell phones, radio and overhead projector were the available at the distance learning centre while few of the respondents indicated that slides and charts were not available. Furthermore, most of the respondents noted multimedia resources such as mobile/cell phones, the internet services, computers, television and camera were highly utilized at the centre while CD was never used. Limited access to multimedia resources, lack of knowledge to use the multimedia, uncooperative instructor to facilitate easy access, time consuming were some of the identified challenges encountered. Originality/Value: It was recommended that there should be a general awareness about the multimedia resources at study centre and that funds should be adequately provided to acquire these resources. Also, university management should consider developing a functional policy that will guide and improve multimedia resources usage at the study centre.